A polêmica como interincompreensão no discurso da política acadêmica da Universidade Federal do Pará - PANTOJA, Benedito José Brabo (2010)
The universities, besides its constitutionally foreseen attributions of education, research and extension, possess a forth essential element which is inseparable from the others, materializing in the intense political practice developed in the academic environment. Given the existence of this factor, this research examines the phenomenon of the polemic as element of interincomprehension in the confrontations of the academic politics in the Federal University of Pará (UFPA), with the main theoretical support based in Maingueneau (2005), observing how this relation of interincomprehension is established, by means of analysis of the simulacra that each subject constructs of his interlocutor and himself. The corpus of this work is constituted by, on the one side, the notes of the three academic entities of the UFPA, which are the Students Central Directory - DCE, the UFPA Professor Association - Adufpa and the UFPA Worker Union - Sintufpa, which represents, respectively, students, professors, and technical-administrative servers; and, on the other side, the notes of the Superior Administration. These notes mention the UFPA administration building took over by the students, occurred in June of 2007, motivated, according to a note by the student entity Attachment 3A), for not having their claims, related to several academic problems, heard. The research is developed in a discursive perspective, whose methodology comprises a general objective, which is to identify the simulacra that are constructed in the academic politics of the UFPA. To do so, four research fronts were used, materialized in specific objectives, namely: (1) to investigate the context of this politics; (2) to rescue the constituent vocabulary of the discursive materiality, observing the actions, referred by means of verbs and names, and the characterizations, effected through adjectivations and names; (3) to identify the marks of the heterogeneity presented; (4) to capture the instants of infraction to the “dogmatic code” of the political practice. Throughout the notes, in the discursive clash that is developed, we perceive the so-called “deaf dialogue”, in which the possibility of the adversaries to review their positioning is not glimpsed.